Randomized Controlled Trial Comparing the Efficacy and Safety of Epidural Infiltration of Particulate Versus Nonparticulate Steroids in the Treatment of Patients with Sciatic Pain - Nazir, Nazia; Gupta, Savita; Saxena, Vikas (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Epidural corticosteroid injections are widely used to treat low back pain, but doubts exist about the relative efficacy of particulate versus non-particulate corticosteroids. Epidural corticosteroid injections were performed in 75 patients with chronic radicular pain were evaluated for epidural corticosteroid injections to determine if there was a difference in the efficacy of triamcilone acetate, methylprednisolone acetate, and dexamethasone. Methods: 75 patients presenting with debilitating radicular pain were randomized to receive an injection of triamcilone acetate 40 mg/ml, methylprednisolone acetate 40 mg/ml, and dexamethasone phosphate 7.5 mg/ml at equal doses. Data were collected at 1-month and 3-month follow-up. The primary outcome of the present study was reduction in pain on a visual analog scale (VAS) at 3 months, while the secondary outcome was the type and number of complications in the study group. Results: Regardless of baseline score VAS, pain score decreased in all patients at one and three months. The patients with VAS of very severe also showed a statistically significant success rate at one and three month follow-up [p= 0.043]. No serious complications occurred in all three groups. Conclusion: According to this study, pain relief and functional improvement are similar among all three methylprednisolone acetate, triamcilone acetate and dexamethasone phosphate at 3 months.